A Hands‐on Conceptual Rigour: A Multi‐scalar Approach. (1st March 2023) - Spiller, Neil
Abstract: AD Editor Neil Spiller first met Dwayne Oyler and Jenny Wu, founders of the Oyler Wu Collaborative, in 2014. Since then he has been interested in their practice, buildings and teaching, and their application of multi‐scalar solutions to projects from jewellery to urban towers, memorials and stairways. Here he talks to them about their recent designs, and the ambience and competitive nature of practising in Los Angeles.